Artificial breeding and culture of the crown-of-thorns starfish Acanthaster planci (Linnaeus, 1758) larvae in China. Issue 3 (3rd July 2017) - Tian, Yushun; Yu, Zonghe; Luo, Peng; Yun, Long; Huang, Wen; Hu, Chaoqun; Huo, Da; Li, Huo
Abstract: Though the breeding and the rearing of Acanthaster planci larvae had been reported before, the descriptions of them are not all-around, and there are no clear and detailed pictures indicating the whole process of embryonic and larval development. Besides, some methods described previously for culturing A. planci larvae are troublesome and even not available. In this study, adult A. planci were artificially induced to spawn and fertilized eggs were incubated and cultured indoor with disinfected seawater. A. planci developed from fertilized eggs to early bipinnaria by 50 h. Once a large number of late brachiolaria occurred, the diets were replaced by mixed benthic diatoms on settlement plates. Five-armed juveniles were reached after 23-day rearing when enough live Chaetoceros mueller and oceanic red yeast were supplied. It is critical to prevent infections by protozoa and pathogenic bacteria. The diets used here are universal in larval rearing and easily obtainable, which guarantees constant supply of diets and thus largely increases the successful rate of the rearing. Artificial breeding and culture of A. planci larvae not only enriched the knowledge on the spawning, larval culture, and developmental process of A. planci but also provided abundant materials to facilitate various studies.